2022
DOI: 10.2478/acee-2022-0046
|View full text |Cite
|
Sign up to set email alerts
|

Tap Water Purification Using Pitcher Filters

Abstract: Due to the high risk of exposure to various contaminants in drinking water, pitcher filtration is rapidly growing in popularity worldwide as a cheap and easy method to remove pollutants from drinking water. On the other hand, an evaluation of the real-time performance of pitchers is not possible for usual consumers. This study presents the performance of pitcher filtration in the removal of copper, chlorine, and chloroform from tap drinking water. Pitchers were packed with Aquaphor cartridges JS500, A5, and B2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…According to the authors, the different changes in pH values are due to the different filtering media. Krolag et al [17] also report a decrease in the pH of filtrates from pitcher filters designed to decrease water hardness. Apart from the difference in pH values, they also observed a stronger decrease in conductivity (35%) from groundwater and well samples compared to our results.…”
Section: Influence Of the Pitcher Filters On The Electrical Conductiv...mentioning
confidence: 96%
See 1 more Smart Citation
“…According to the authors, the different changes in pH values are due to the different filtering media. Krolag et al [17] also report a decrease in the pH of filtrates from pitcher filters designed to decrease water hardness. Apart from the difference in pH values, they also observed a stronger decrease in conductivity (35%) from groundwater and well samples compared to our results.…”
Section: Influence Of the Pitcher Filters On The Electrical Conductiv...mentioning
confidence: 96%
“…Contrary to our results Al-Haddad et al [21] observed a reduction in the concentrations of major cations and anions, including NO3, only in the case of reverse osmosis, but not in the case of pitcher filters. Krolag et al [17] report more than 80% reduction in the amount of nitrates in the treated waters after filtration with pitcher filters. Their results are close to the value we obtained after two consecutive filtrations of the model water.…”
Section: Removal Efficiency Of Phosphate Phosphorus and Nitrate Nitro...mentioning
confidence: 98%